2018
DOI: 10.1371/journal.pone.0205703
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interactions among metabolic syndrome components on the development of cardiovascular disease among Kazakhs in Xinjiang

Abstract: BackgroundFew prospective studies have explored the effect of interactions among metabolic syndrome (MS) components on the development of cardiovascular disease (CVD) in the Kazakh population in Xinjiang Province of China.MethodAs of December 2016, 2,644 participants who completed a baseline survey over a period of 5 years or more were included in the study. The multiplicative interactions among MS components were evaluated by incorporation of the product terms into a logistic regression model. The additive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The measuring tape was used to measure waist circumference (WC) in cm to the nearest 0.1 cm around the abdomen at the level of the umbilicus (belly button). Central obesity was defined as WC>90 cm for males and 80 cm for females [21]. WHR was calculated to find abdominal obesity.…”
Section: Methodsmentioning
confidence: 99%
“…The measuring tape was used to measure waist circumference (WC) in cm to the nearest 0.1 cm around the abdomen at the level of the umbilicus (belly button). Central obesity was defined as WC>90 cm for males and 80 cm for females [21]. WHR was calculated to find abdominal obesity.…”
Section: Methodsmentioning
confidence: 99%
“…The pathogenesis of MetS is complex and the effects of MetS components are usually correlated [ 33 ]. Therefore, some studies have assessed and reported synergistic interactions between MetS components and other health outcomes, such as insulin resistance [ 44 ], cardiovascular disease [ 45 ], and diabetes mellitus [ 46 ]. Taken together, the cluster of MetS components had a synergistic harmful effect on not only vascular outcomes but also successful aging.…”
Section: Discussionmentioning
confidence: 99%
“…The database construction and some statistical analyses have been previously described [ 12 ]. Cox proportional hazards regression model was used to evaluate the association of each component and the number of combinations of MS components on the development of CVD.…”
Section: Methodsmentioning
confidence: 99%
“…Next, we evaluated the interactions between TG and WC, TG and BP, WC and BP. The grouping method and additive interactions have been previously described [ 12 ]. Multiplicative interactions among BP, WC, and TG were evaluated by incorporation of the dummy variable into a Cox regression model.…”
Section: Methodsmentioning
confidence: 99%